Desenvolvimento de projetos de sistemas fotovoltaicos com auxilio do software MATLABTM - Silva, Villian Lafayette Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this job was to develop a design of solar photovoltaic systems in the configurations of autonomous network or connected to the electric grid through the platform of MATLABTM. Allowing the user to perform a demand survey to size the necessary equipment of a photovoltaic system such as battery bank, inverter, cable and solar panel design. Based on the methodology identified and following the methods according to NBR 5410: 2004, an algorithm was developed that covers all the parameters used to size a solar system in its complexity, dividing the type of system adopted by the user and the type of selected (110V or 220V).
Monografia
Keywords: Matlab; Algoritmo; Sistemas fotovoltaicos; Sizing; Algorithm; Solar systems; ENGENHARIAS::ENGENHARIA ELETRICA